The relation of coastal geomorphology to larger mass strandings of odontocetes around Australia - Hamilton, L. J.; Lindsay , K. (J. Cetacean Res. Manage., 2023)
Sites of larger live mass strandings (10 to 250 individuals) for five selected odontocete (toothed whale) species around Australia are examined to see if they have any characteristics or properties which might be related to the strandings. Bays are the significant coastal unit in the 66 events reported over a 100 year period; only three events were not within bays but on open sandy coastlines. Species, species adult size and bay size do not appear to be factors in these larger stranding events. The reason for the association of bays with larger mass strandings is not obvious. Many of the bays have simple planform and uncomplicated bathymetry. However, they share some properties previously associated with strandings that are a consequence of the processes of bay formation. Coastal locations other than particular types of bays do not necessarily have all of these properties, potentially explaining why these bays dominate the Australian mass stranding record. A chain of geomorphological, physical, and biological factors can be constructed to explain the role of the bays in mass strandings. Regardless of this possible explanation, there is an observed correlation of particular site properties with larger live mass strandings about Australia which might be expected to have predictive power in indicating potential mass stranding sites. This is particularly apparent when key properties of stranding sites are defined and compared in terms of simple quantitative thresholds. The sites of herd strandings around New Zealand generally exhibit the expected properties.